Kinetic Modeling of Biogas Generation from Banana Stem Waste - Jailani, Salihon; N., Zainol (Springer, 2012)
A kinetic model for biogas generation from banana stem waste was proposed on the basis of the obtained experimental results. The system consists of an anaerobic sequencing batch reactor for the ﬁrst stage and an anaerobic ﬁxed bed reactor for the second stage, which is operating at hydraulic retention times (HRT) of nine days. The process was conducted at ambient temperature for the ﬁrst stage and thermophilic temperature for the second stage. Four differential equations described the overall process. This study employed ﬁrst order kinetics for hydrolysis of non-soluble organic matter and a Michaelis–Menten equation type for the soluble organic matter decomposition, total volatile acids consumption and methane production. The following kinetics constants were obtained for the above- mentioned anaerobic stages: (a) hydrolysis and solubilization of organic matter: k (kinetic constant for non-soluble organic matter degradation): 0.0037 day -1 1 ;k 2 (maximum rate of soluble organic matter production): 0.0241 g soluble chemical oxygen demand (SCOD)/l day; k (saturation constant): 0.0236 g SCOD/l; (b) acidogenesis: k 4 3 (maximum rate of soluble organic matter degradation): 0.0086 g SCOD/l day; k (saturation constant): 0.0189 g SCOD/l; and (c) methanogenesis: k65 (maximum rate of acetic acid (TVA) consumption): 0.0092 g TVA/l day; and k7 (saturation constant): 0.0003 g TVA/l. The kinetic constants obtained and the proposed equations were used to simulate the different steps of the anaerobic